Distribution and removal characteristics of microplastics in different processes of the leachate treatment system. (1st February 2021) - Zhang, Zhongjian; Su, Yinglong; Zhu, Jundong; Shi, Jianhong; Huang, Huang; Xie, Bing
Graphical abstract: Highlights: Fibers and PE were major shape and polymer type of MPs in the leachate treatment. The ultrafiltration had the highest efficiency of removing MPs (75%). The Nanofiltration and Reverse Osmosis had no effect on MPs removal. The sludge was the major receiver of the MPs removed from leachate. Abstract: Microplastics (MPs) in environments are widely concerned in recent years due to the widely occurrence and potential risk to environments. With a large amount of plastic waste discarded into the landfills, leachate generated from landfills was found to be an important pollution source of MPs. However, the removal efficiency and characteristics of MPs in leachate treatment system were not clear. In this study, the concentration variation and the removal performance of MPs in leachate treatment system with the process of pretreatment + biotreatment + advanced treatment were investigated. The results showed that 58.33% of MPs were removed during the leachate treatment process. The Ultrafiltration had the highest efficiency of removing MPs, but the advanced treatment technologies (Nanofiltration and Reverse Osmosis) did not contribute to the removal of MPs. Furthermore, the removal performance of MPs in leachate treatment process was determined by MPs properties, such as size, shape and polymer type. The whole leachate treatment process had higher removal efficiencies for particle MPs compared to fiber MPs, and only 50% of fiber MPs were removed in biological treatment and advanced treatment. Ultrafiltration had better removal effect on microplastics with the size of less than 1 mm, and MPs less than 0.5 mm were almost removed by advanced treatment but accumulated in the sludge with the abundance of 0.893 ± 0.252 items/g. The results showed that a considerable amount of MPs (10 6 items/day) discharged with the effluent (3200 t/d), and most removed MPs from leachate accumulated in sludge, which would cause potential risk to the environments.